Monday

July 28, 2014

July 28, 2014

Posted by **Molly** on Wednesday, February 19, 2014 at 8:34pm.

- algebra -
**Henry**, Saturday, February 22, 2014 at 3:53pm2x - 3y = 3

-3y = -2x + 3

Y = (-2/3)x - 1. Slope-intercept form.

I don't know which form you want.

- algebra -
**Henry**, Saturday, February 22, 2014 at 3:55pmCorrection: Y = (2/3)x - 1.

**Related Questions**

algebra - What is an equivalent form of the following equation 2x-3y=3

algebra - Simplify the following expression, and rewrite it in an equivalent ...

math - hi, i need help with solving this equation for "y" 2x+3y=-2 2x+3y=-2 Get ...

Algebra - Rewrite the equation 2x+4y+2=3y+5 in general form. A.2x+y-3=0 C.2x+y=3...

Math - Explain how to solve? Which equation below shows the equation y = – 1/4x...

bobpursly,.math - Ok, assume it equals zero. 2x + 3y -6=0 subtract 3y from each ...

Algebra 2 - If you were to use the substitution method to solve the following ...

algebra - I need a step by step explanation on how to add these two equations 2x...

correction of math - rewrite the equation 2x-3y= -6 as a function of x. My ...

math - 2x+3y=6 (solve for x) 2x+3y=6 Get unknown on one side and everything else...